Adrenal High‐Expressional CYP27A1 Mediates Bile Acid Increase and Functional Impairment in Adult Male Offspring by Prenatal Dexamethasone Exposure - Jiangang Cao; Wen Hu; Yawen Chen; Aihemaitijiang Ailikaiti; Ziyi Zhang; Lingbo Rong; Hong Yu; Hui Wang (Advanced Science)
Abstract Prenatal dexamethasone exposure (PDE) can impact adrenal corticosteroid synthesis in adult offspring. Furthermore, the adrenal gland can autonomously synthesize bile acids, but local bile acids accumulation has cytotoxic effects. This study found that PDE increased histone 3 lysine 27 acetylation (H3K27ac) levels in the promoter region of cholesterol 27 hydroxylase (CYP27A1) and its expression, as well as total bile acids (TBA) concentrations and enhanced endoplasmic reticulum stress (ERS) and inhibit steroid synthesis in adult male offspring rat adrenal glands. However, it is reversed in females. Tracing back to the prenatal stage and in combination with cellular experiments, it is further revealed that dexamethasone can regulate glucocorticoid receptor (GR)/SET binding protein 1 (SETBP1)/CYP27A1 signal pathway, consequently cause intracellular increase of bile acids. Finally, administration of nilvadipine (CYP27A1 inhibitor) to male offspring for 4 weeks after birth resulted in the reversal of PDE‐induced adrenal morphological and functional damage. In conclusion, PDE induces fetal adrenal corticosteroid dysfunction in adult male offspring by upregulating CYP27A1 promoter region H3K27ac levels and expression in the adrenal gland through the GR/SETBP1 signaling pathway. This effect persists beyond birth, leading to bile acids local increase and subsequent enhancement of ERS, ultimately inducing cellular dysfunction in adult adrenal glands.